Peran Strategis Notaris dalam Pembuatan Akta Perjanjian Waralaba untuk Kepastian dan Perlindungan Hukum Para Pihak - Sendee Theresia Suriadiningrat; Ismala Dewi; Pieter E. Latumeten (Jurnal Ilmiah Kebijakan Hukum, 2025)
Franchise agreements play a pivotal role in the advancement of the franchise business in Indonesia. However, these agreements often lead to differing interpretations and have weak evidentiary power because only created as private deeds. In the relevant regulations, there is no provision that requires it to be made in the form of an authentic deed. In fact, an authentic deed offers the necessary evidentiary strength to protect the rights of all parties involved. Notaries are legally empowered to draft authentic deeds and provide legal advice and its possible implications. This research is doctrinal with a prescriptive approach, aiming to examine the use of authentic deeds in franchise agreements to ensure legal protection. The goal is to reduce disputes and legal exploitation that can occur with private deeds. Through the analysis of secondary data and interviews, it is a fact that disputes often occur due to differences in the interpretation of the content of the agreement. Therefore, franchise agreements should be executed as authentic deeds rather than just private deeds. This practice is significant because franchise agreements include fundamental elements like the rights and obligations of the parties, as well as intellectual property rights elements, such as trademarks and trade secrets. In fact, the use of authentic deeds is not intended to seek validity but to seek the value of legal certainty.